Gambaran Pemeriksaan Laju Endap Darah Pada Penderita Anemia Di Rumah Sakit Umum Wisata Universitas Indonesia Timur Makassar - Jurnal Syarif (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Anemia is a symptom of underlying conditions, such as loss of blood components, lack of nutrients needed for blood cell formation resulting in decreased oxygen-carrying capacity of blood. This study aims to find out the results of examination rate of blood vapor in anemic patients at General Hospital Tourism University of Eastern Indonesia Makassar. Type of This Research Is Laboratory Observation, The sample in this study is anemia patients as many as 5 Samples.From the result of research which have been done at General Hospital of Universitas Indonesia Timur Makassar on 5 samples, the result is 40% -60% mm / h, 40% is normal limit while 60% is increased. Based on the above research results, it is suggested for the community, especially parents can pay more attention and maintain the intake of nutrition and healthy lifestyle.